Differences in maternal role attainment in stunting prevention in rural and urban areas of Jember regency - Dwi Indah Lestari; Ayesie Natasa Zulka; Muhammad Zainullah (Jurnal Keperawatan, 2024)
Introduction:  The sociodemographic conditions of Jember Regency can shaped the role attainment of mothers in preventing stunting. The Maternal Role Attainment theory, explains that the mother's role attainment was influenced by 3 factors, namely the macrosystem, mesosystem and microsystem. Objectives:  The purpose of this study was to analyze differences in maternal role attainment in rural and urban areas of Jember Regency. Methods: The research design used was  descriptive analytical with a cross sectional approach.  Total sample of 215 mothers who met the inclusion criteria was selected using the multistage random sampling technique. Data were analyzed using  Mann Withney U Test with α = 0.05. Results:  there was a difference between the role attainment of mothers in rural and urban areas (0.032<0.05). Conclusions:  Based on the theory of maternal role attainment, differences in maternal role attainment in rural and urban areas were influenced by macrosystems, mesosystems, and microsystems as well as components of the mother's self. Further research can analyze the determinant factors in the differences in role attainment.